BEBERAPA KONSEP YANG BERKAITAN PADA RUANG FUZZY BERNORMA DAN RUANG FUZZY BERNORMA-n - Mashadi Mashadi (Universitas Jenderal Soedirman, 2012)
In this paper we will discuss some of the approaches of fuzzy normed spaces and development on fuzzy n-normed space. The approach discussed is based on the concept of t-norm and-t conorm and directly as well as defining the usual definition normed space. But it is discussed in more detail in this paper is the definition that refers to a generalized regular normed spaces on fuzzy 2-normed space and space and fuzzy n-normed space.